PENGARUH IMBANGAN TEPUNG TEMPE DAN TERIGU TERHADAP KARAKTERISTIK ROTI TAWAR - Raden Haerudjaman (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2021)
Indonesia is seen as one of the rich countries in the field of traditional fermentation technology. Of the various types of fermented food, tempeh is a kind of food most outstanding views from simple technology, high nutritional value, and economically relatively cheap (Winarno, 1985). Tempe can be processed into flour. Advantages of flour products than can be saved in the long term, can also be processed into various forms of processed foods, so that the use of tempe become more multipurpose (Sarwono, 1996). One alternative is to add tempeh flour utilization in the manufacture of bread, so that the nutritional value of protein bread can rise. Making bread using flour mixture involves a problem particularly on the physical characteristics of the resulting bread, therefore it is necessary to investigate the influence of the balance of tempeh flour and wheat flour to the characteristics of the resulting bread, especially organoleptic properties such as taste and appearance. Preliminary experiments have been conducted to try different counterweight soybean and wheat flour baking test from 5: 95, 10: 90, 15: 85, 20: 80, 25: 75, 30: 70, 35: 65, 40: 60, 45: 55, 50: 50, on trial introduction that has been done shows that the rate of bread with a proportion ranging from 30: 70 to 50: 50 provides a value which is not preferable in terms of color, aroma, taste, porosity and texture. Based on these descriptions, then to set the balance of the primary research that will be examined starting from 0: 100 to 25: 75. The experiment was conducted at the Laboratory of Food Teknology Agricultural Faculty Ma’soem University, starting in Juny 2021 using a randomized block design (RAK). Based on the results obtained during the study, it can be concluded that the soybean flour is added to the bread dough will affect the characteristics of the resulting bread. Balance of tempeh flour: wheat 10% (10:90) to produce the best characteristics of white bread with a moisture content of 33.4%, protein content 9.79%, ash content 0:33% or organoleptic properties of bread produced acceptable panelists.